Recent advances in nanocarrier-based targeted drug delivery: For lung, colon, and breast cancers - Sabouri , Parisa; Bahadori, Sogand; Mohsennejadesaniyani, Azam; Hosseini, Seyed Mohammad Reza; Khodamorovati, Mahbod; Yazdani, Erfan; Mohammadi, Dina; Nejadkoorki, Darya; Sulashvili, Marika; Tavamaishvili, Ketevan; AbdulSattar, Husain; James John, Johan; et al. (Journal of Composites and Compounds, 2023)
For a while now, the development of research and technology has provided us with different approaches which show how cancer works and how is it possible to develop different methods of treatment. Nanotechnology and nano-carriers have shown a promising approach toward the treatment of different types of cancer. Nano-carriers based targeted drug delivery have different forms such as lipid-based, polymeric-based, inorganic-based, and hybrid-based, each of them is unique in structure, size, “function and” ability to deliver the drugs. Therapeutic substances can be used with the help of the applied modifications to the nano-carriers. These particles have shown significant benefits such as effectiveness, safety, low toxicity, biocompatibility, biodegradability and the improved quality of the treatment. The therapeutic properties of the nano-carriers can be regulated. This can help to provide an effective treatment for a patient with a specific diagnosed disease. The treatments can be administered either orally, intravenously or by combined route. The overall results of the use of nano-carriers have certainly created an interesting approach and created an opportunity for new treatments that improve the patient’s profile.